Hipotesis pasar efisien: tinjauan pustaka sistematik - Listika Zen, Emi (Fair Value: Jurnal Ilmiah Akuntansi dan Keuangan, 2022)
In recent years, academics and economists have studied the concept of efficiency as applied to capital markets, the efficient market hypothesis (EMH) being a major research area in the specialization literature. They have opposing views about EMH, some are against EMH, some are in favor of EMH. The efficient market hypothesis states that the price of any asset depends on the information, whereas the behavioral finance theory states that the price depends on the reaction of market participants to the information. The conclusion of this article is that testing market efficiency is difficult and it is likely that due to changes in market or economic conditions, new theoretical models should be developed to take into account all changes. For this reason, it is important to continue empirical studies to decide whether capital markets are efficient or informationally inefficient.